2012
DOI: 10.1155/2012/381328
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control after Total Pancreatectomy for Intraductal Papillary Mucinous Neoplasm: An Exploratory Study

Abstract: Background. Glycemic control following total pancreatectomy (TP) has been thought to be difficult to manage. Diffuse intraductal papillary mucinous neoplasm (IPMN) is a potentially curable precursor to pancreatic adenocarcinoma, best treated by TP. Objective. Compare glycemic control in patients undergoing TP for IPMN to patients with type 1 diabetes mellitus (DM). Design/Setting. Retrospective cohort. Outcome Measure. Hemoglobin A1C(HbA1C) at 6, 12, 18, and 24 months after TP. In the control group, baseline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
1
26
0
2
Order By: Relevance
“…The median number of rapid-acting insulin units reported for previous studies ranged 18-21 U. The requirement for insulin was usually less than expected after TP because of an increase in the expression of peripheral insulin receptors [49][50][51] . In previous studies, it was reported that patients with apancreatic diabetes required less insulin per day compared to those with type 1 DM [52][53][54] .…”
Section: Endocrine and Exocrine Replacement After Tpmentioning
confidence: 96%
See 1 more Smart Citation
“…The median number of rapid-acting insulin units reported for previous studies ranged 18-21 U. The requirement for insulin was usually less than expected after TP because of an increase in the expression of peripheral insulin receptors [49][50][51] . In previous studies, it was reported that patients with apancreatic diabetes required less insulin per day compared to those with type 1 DM [52][53][54] .…”
Section: Endocrine and Exocrine Replacement After Tpmentioning
confidence: 96%
“…The similarities between the glycated hemoglobin levels of patients who underwent TP and PD, and the episodes of hypoglycemia or ketoacidosis showed no evidence that diabetes control was worse in patients who underwent TP [59] . Jamil et al [49] and Casadei et al [46] reported that glycemic control after TP could be managed well. In ad- 146 dition to improved endocrine control, exocrine insufficiency might be improved using modern pancreatic enzyme formulations and pylorus-preserving or subtotal stomach-preserving TP [14,60] .…”
Section: Endocrine and Exocrine Replacement After Tpmentioning
confidence: 99%
“…concentrations can be kept within a tolerable range after total pancreatectomy by the usage of well-established long-acting insulin formulations. 37 Further studies with long-term follow-up data of patients who undergo total pancreatectomy for premalignant pancreatic tumors are needed.…”
Section: Figurementioning
confidence: 99%
“…Many believe these to be insurmountable barriers to expanding the role of TP, but ongoing advances in technology, pharmaceuticals and management strategies are changing the outlook for life after pancreatectomy. Once considered to be 'brittle' diabetics, many studies now show that TP patients experience no difference in diabetes-specific complication rates or long-term glycemic control compared to type 1 diabetics [42][43][44] . Moreover, pancreatic enzyme replacement therapy has improved GI symptoms and largely resolved nutritional deficiency in appropriately managed patients [38,45] .…”
Section: Discussion: Who Should Undergo Tp For Ipmn?mentioning
confidence: 99%